2010
DOI: 10.5194/acp-10-10895-2010
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the complex local-scale flows influencing ozone patterns in the southern Great Lakes of North America

Abstract: Abstract. This study examines the complexity of various processes influencing summertime ozone levels in the southern Great Lakes region of North America. Results from the Border Air Quality and Meteorology (BAQS-Met) field campaign in the summer of 2007 are examined with respect to land-lake differences and local meteorology using a large array of ground-based measurements, aircraft data, and simulation results from a high resolution (2.5 km) regional airquality model, AURAMS.Analyses of average ozone mixing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 50 publications
1
62
0
Order By: Relevance
“…6) shows that when particle concentrations increased on 6 July there was a northwest to north flow crossing the Detroit and Windsor areas. Local emissions thus played a greater role during this part of the period compared to the first episode, but the location of their impact varied depending upon the synoptic wind direction and lake breezes (Levy et al, 2010). This is discussed further below.…”
Section: Meteorology and Air Quality During The Intensive Periodmentioning
confidence: 97%
See 4 more Smart Citations
“…6) shows that when particle concentrations increased on 6 July there was a northwest to north flow crossing the Detroit and Windsor areas. Local emissions thus played a greater role during this part of the period compared to the first episode, but the location of their impact varied depending upon the synoptic wind direction and lake breezes (Levy et al, 2010). This is discussed further below.…”
Section: Meteorology and Air Quality During The Intensive Periodmentioning
confidence: 97%
“…The lake breeze from Lake Erie, as well as the prevailing synoptic winds, impacted the spatial and temporal heterogeneity in O 3 and PM 2.5 . Levy et al (2010) showed that emissions in the Detroit-Windsor area contributed significantly to the high O 3 at Harrow on the 6th with Lake Erie playing an important role. Under northerly winds the Detroit River and western Lake Erie first played a role early on the day by funnelling and accumulating the emissions and secondary products from the Detroit-Windsor area.…”
Section: Meteorology and Air Quality During The Intensive Periodmentioning
confidence: 99%
See 3 more Smart Citations